Long-Term Reversible Contraception in Adolescence: The Reality of a Tertiary Pediatric Hospital in Portugal - Ferro, Beatriz (2023)
Introduction: Contraception in adolescence is essential to prevent unwanted pregnancies, abortion and sexually transmitted diseases. The use of longacting reversible contraceptive methods (LARCs) has been highly recommended due to their efficacy since they are user independent methods. The aim of this study was to evaluate the use of LARCs in adolescence in the population of a Childhood and Adolescence Gynecology clinic, and to describe the sociodemographic characteristics of the adolescents as well as previous contraceptive practices.Material and Methods: Retrospective analysis that included adolescents using LARCs, monitored in a Childhood and Adolescence Gynecology clinic of a Portuguese tertiary pediatric hospital, between June 2012 and June 2021.Results: A total of 122 adolescents were included, with a median age of 16 (11 – 18) years and 62.3% (n = 76) were sexually active. The preferred method was the subcutaneous implant, placed in 82.3% (n = 101), followed by the Levonorgestrel-Intrauterine System in 16.4% (n = 20) and the copper intrauterine device in 1.3% (n = 1). The main indications for LARCs were contraceptive needs 90.2% (n = 110), abnormal uterine bleeding during puberty in 14.8% (n = 18), dysmenorrhea in 10.7% (n = 13) and need for amenorrhea in 0.8% (n = 1). The median time of implant use was 20 (1 – 48) months and of the LNG-IUS it was 20 (1 – 36) months. The 12-month adherence rate for both was 76.2% (n = 93). The removal rate for reasons besides the expiration date was 9.8% (n = 12) in adolescents who had implants, and no LNG-IUS or copper intrauterine devices were removed. There were no pregnancies after insertion of LARCs.Conclusion: Contraceptive needs were the main reason for choosing LARCs, followed by abnormal uterine bleeding during puberty management and dysmenorrhea. All these factors may contribute to the high rate of satisfaction and continuity of these methods.